A terbium-based target material and preparation method thereof, rare earth permanent magnet, and new energy vehicle
The terbium-based target is prepared by powder metallurgical atmosphere sintering method, which solves the problems of uneven grains and looseness in the smelting and casting method, and realizes the terbium-based target with high density and low oxygen content, which improves the magnetic properties of the neodymium-ferbor magnets. It can and the performance of new energy vehicle motors.
Patent Information
- Application Number
- CN202411493857.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing smelting and casting methods have problems of uneven grains, shrinkage and looseness, and it is difficult to accurately control the casting temperature and flow rate, resulting in unstable magnetic properties.
By using powder metallurgical atmosphere sintering method, terbium powder is mixed with the reducing agent ball mill, spray the finer slurry after isostatic molding, sintering and microcrystallation annealing treatment, forming a high-density, uniform and fine terbium-based target material .
The high relative density and low oxygen content of the terbium-based target are achieved, the magnetic performance of the target and the energy conversion efficiency of the motor are improved, the grain boundary diffusion effect is improved, and the magnetic performance of the neodymium iron boron magnet is significantly improved.
Smart Images

Figure CN118996360B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of target material preparation, and in particular relates to a terbium-based target material and a preparation method thereof, a rare earth permanent magnet, and a new energy vehicle. Background Art
[0002] The booming development of new energy, intelligent manufacturing and new generation mobile communications has greatly increased the demand for advanced motors and put forward higher requirements for the output performance of motors. In NdFeB permanent magnet motors, the magnetic properties of NdFeB magnets largely determine the output performance of the motor. The magnetic properties of NdFeB magnets are usually improved through grain boundary diffusion technology, that is, using terbium (Tb) / dysprosium (Dy) target as raw material, using magnetron sputtering equipment to deposit terbium / dysprosium on the surface of NdFeB magnets, and then heat-treating, so that terbium / dysprosium penetrates into the interior of NdFeB magnets through grain boundary diffusion, thereby improving the magnetic properties of NdFeB magnets.
[0003] At present, terbium targets are mainly prepared by melting and casting methods, and their quality is easily affected by many factors such as pouring head design, pouring temperature, pouring flow rate, and the speed of melt cooling. In particular, the cooling speed of terbium melt is fast, and the state of terbium melt needs to be observed at all times to adjust the casting flow rate, which makes it difficult to accurately grasp the pouring temperature and flow rate. If the pouring temperature is too low, the fluidity of the terbium melt will be poor. If the pouring temperature is too high, the shrinkage of the terbium melt will increase. Both will cause shrinkage compensation difficulties and form defects such as shrinkage cavities and looseness. And too high a pouring temperature will also promote excessive grain growth. In addition, if the pouring flow rate is too fast, the cooling speed will be too slow, which is easy to cause coarse grains. If the pouring flow rate is too slow, the cooling speed will be too fast, which is easy to cause fine grains, resulting in poor uniformity.
[0004] Therefore, it is necessary to develop a powder metallurgy atmosphere sintering method to prepare highly uniform and dense terbium targets. Summary of the invention
[0005] The purpose of the present application is to provide a terbium-based target material and a preparation method thereof, a rare earth permanent magnet, and a new energy vehicle, aiming to solve the problems of uneven grains, shrinkage cavities, and looseness of the terbium target material produced by the existing smelting and casting methods.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a method for preparing a terbium-based target, comprising the following steps:
[0008] ball-milling the first terbium powder, the second terbium powder and the reducing agent to form a mixed powder;
[0009] isostatically pressing the mixed powder to obtain a first green body;
[0010] Spraying a refiner slurry onto the surface of the first green body and then sintering the green body to obtain a second green body;
[0011] The second green body is subjected to microcrystallization annealing treatment, and then machined to obtain a terbium-based target material.
[0012] In a second aspect, the present application provides a terbium-based target material, which is prepared by the preparation method of the terbium-based target material provided by the present application; wherein the oxygen content of the terbium-based target material is lower than 1000 ppm and the relative density is higher than 98.5%.
[0013] In a third aspect, the present application provides a rare earth permanent magnet, comprising a NdFeB magnet and a terbium-based metal layer deposited on the surface of the NdFeB magnet, wherein the terbium-based metal layer is obtained by sputtering and coating the terbium-based target provided by the present application.
[0014] In a fourth aspect, the present application provides a new energy vehicle, including a motor, wherein the motor includes the rare earth permanent magnet provided in the present application.
[0015] Compared with the prior art, this application has the following beneficial effects:
[0016] (1) The added reducing agent decomposes to generate hydrogen during the sintering process, providing a reducing environment, preventing terbium oxidation, and ensuring the purity of terbium metal in the target material, thereby helping the terbium in the target coating to diffuse into the RuFeB magnet through the grain boundary, thereby improving the magnetic properties of the RuFeB magnet.
[0017] (2) Spraying a refiner slurry on the surface of the first green body to form high grain boundary strength during the sintering process, improve the density and heat resistance of the green body, thereby inhibiting grain growth and making the target material grain structure more uniform and fine.
[0018] (3) Microcrystallization annealing treatment of the second green body can promote grain refinement, thereby further improving the density of the target material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0020] Figure 1 is a process flow chart of a method for preparing a terbium-based target material provided in an embodiment of the present application;
[0021] Figure 2 This is a SEM image of the terbium-based target prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0022] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0023] The first aspect of the present application provides a method for preparing a terbium-based target material, such as Figure 1 As shown, the following steps are included:
[0024] S01: ball-milling the first terbium powder, the second terbium powder and the reducing agent to form a mixed powder;
[0025] S02: isostatically pressing the mixed powder to obtain a first green body;
[0026] S03: spraying the refiner slurry onto the surface of the first green body and then sintering the green body to obtain a second green body;
[0027] S04: performing microcrystallization annealing treatment on the second green body, and then machining to obtain a terbium-based target material.
[0028] The preparation method of the terbium-based target provided in the embodiment of the present application, by adding a reducing agent, decomposes and generates hydrogen during the sintering process, provides a reducing environment, prevents terbium oxidation, and ensures the terbium metal purity of the target material, thereby helping the terbium in the target coating to diffuse into the RuFeB magnet through the grain boundary, thereby improving the magnetic properties of the RuFeB magnet. By spraying a refiner slurry on the surface of the first blank, a high grain boundary strength is formed during the sintering process, the compactness and heat resistance of the blank are improved, thereby inhibiting grain growth and making the target material grain structure more uniform and fine. Grain refinement is promoted by microcrystallization annealing of the second blank, thereby further improving the density of the target material. Therefore, the terbium-based target material prepared in the embodiment of the present application has the characteristics of uniform and fine grains, high density and low oxygen content.
[0029] In the above step S01, in the embodiment, the weight ratio of the first terbium powder to the second terbium powder is (6~8) / (2~4), the first terbium powder is spherical with a particle size of 2~10μm, and the second terbium powder is flake or irregular in shape with a particle size of 0.5~1μm; the first terbium powder can be produced by aerosolization, which can improve the fluidity and uniformity of the powder, and the second terbium powder can be produced by high-energy ball milling, which can enhance the surface activity of the powder and the bonding strength during sintering, and improve the high-temperature diffusion performance of the terbium-based target. Therefore, this embodiment uses terbium powder raw materials (micron and submicron terbium powder) with different particle size gradients in combination, and optimizes the bulk density and compactness of the powder by controlling the particle size distribution, thereby improving the sintering performance and microcrystallization effect of the target.
[0030] In an embodiment, the oxygen content of the first terbium powder and the second terbium powder is less than 500 ppm, and the metal impurity content is less than 100 ppm.
[0031] In an embodiment, the reducing agent is selected from at least one of calcium hydride, magnesium hydride and aluminum hydride; these reducing agents can decompose during the sintering process to generate hydrogen to form a reducing environment, prevent terbium oxidation, ensure the purity of terbium metal in the target material, and the generated calcium, magnesium, aluminum, etc. can reduce the melting point of the diffusion source, while increasing the wettability between the diffusion source and the surface of the NdFeB magnet, quickly forming a continuous grain boundary phase as a diffusion channel, and promoting terbium diffusion, so (Ca, Mg, Al) 0.1~3 Tb 97~99.9 Co-diffused RuFeB magnets have better magnetic properties than Tb diffused alone.
[0032] In the embodiment, the amount of the reducing agent added is 0.1-3% of the total weight of the first terbium powder and the second terbium powder, and can further be 1-3%. This addition range not only prevents terbium oxidation and ensures high terbium metal purity, but also reduces the melting point of the diffusion source, increases wettability, can quickly form a diffusion channel, promotes terbium diffusion, and does not generate too much Ca, Mg, Al, etc., which will not have a negative impact on the performance of the co-diffused RuFeB magnet.
[0033] The above-mentioned step S02, the step of isostatically pressing the mixed powder includes: vibrating and filling the mixed powder into a silicone or polyurethane mold, placing it in a cold isostatic press, initially pressurizing it to 50~100MPa and holding the pressure for 2~5min, and then pressurizing it to 150~200MPa and holding the pressure for 2~5min to obtain a first green body.
[0034] In the above step S03, in an embodiment, the refiner slurry includes polyvinyl pyrrolidone, hydroxypropyl methylcellulose, polyethyleneimine, carbon powder, refiner and solvent in a weight ratio of (0.5-5) / (2-8) / (1.5-7) / (0.5-2) / (0.5-3) / (75-95). Polyvinyl pyrrolidone can improve the fluidity and dispersibility of the powder and prevent particle agglomeration. Hydroxypropyl methylcellulose can enhance the viscosity between powders, thereby forming a uniform and stable slurry, which is conducive to coating and film formation. Polyvinyl pyrrolidone decomposes during the sintering process, which is also conducive to removing oxygen and impurities on the surface of the green body. The amine group in polyethyleneimine is reducing, and its decomposition during the sintering process can play a reducing role to prevent terbium oxidation. The refiner can form high grain boundary strength during the sintering process, improve the density and heat resistance of the green body, thereby inhibiting grain growth and making the target material grain structure finer and more uniform. Therefore, the specific components and contents of the refiner slurry in this embodiment are coordinated to help form a terbium-based target with low oxygen content, fine and uniform grains and high density.
[0035] In an embodiment, the refiner includes aluminum oxide and silicon nitride in a weight ratio of (2.5-1.5) / 1; with the cooperation of aluminum oxide and silicon nitride, the grain boundary strength formed is stronger, thereby achieving a better effect of inhibiting grain growth.
[0036] In an embodiment, the solvent is selected from ethanol or terpineol.
[0037] In an embodiment, the sintering treatment steps include: under vacuum or inert atmosphere conditions, first heating to 700-900°C and keeping warm for 6-12 hours, then continuing to heat to 1050-1150°C and keeping warm for 12-24 hours, and then cooling down to below 50°C at a rate of 40-60°C / h.
[0038] In the above step S04, in the embodiment, the atmosphere of the microcrystallization annealing treatment is a mixture of water vapor and nitrogen, the temperature is 800~900℃, and the time is 2~3h; wherein the volume content of water vapor in the mixture is 1~10%. The water vapor in the mixture can heat the blank quickly and evenly, promote grain boundary migration, refine the grains, and at the same time regulate the reaction rate, making the crystallization process more controllable, so that the terbium-based target material is more uniform and dense. In addition, water vapor reacts with carbon powder to generate hydrogen and carbon monoxide, creating a reducing environment, thereby preventing oxidation of the blank surface, thereby avoiding problems such as overheating, deformation, and surface oxidation in other heat treatment methods.
[0039] A second aspect of an embodiment of the present application provides a terbium-based target material, which is prepared by the preparation method of the terbium-based target material provided by the embodiment of the present application; wherein the oxygen content of the terbium-based target material is lower than 1000 ppm and the relative density is higher than 98.5%.
[0040] The terbium-based target material provided in the embodiment of the present application is prepared by the preparation method provided in the embodiment of the present application, so the target material has low oxygen content, uniform and fine grains, and high density, which helps to improve the coating quality of the terbium-based target material and improve the grain boundary diffusion effect.
[0041] A third aspect of an embodiment of the present application provides a rare earth permanent magnet, comprising a NdFeB magnet and a terbium metal layer deposited on the surface of the NdFeB magnet, wherein the terbium metal layer is obtained by sputtering and coating the terbium-based target material provided by the present application.
[0042] The rare earth permanent magnet provided in the embodiment of the present application has a terbium metal layer on its surface obtained by sputtering and coating the terbium-based target provided in the embodiment of the present application, so the magnetic properties of the neodymium iron boron magnet can be significantly enhanced after grain boundary diffusion heat treatment.
[0043] A fourth aspect of an embodiment of the present application provides a new energy vehicle, including a motor, which includes the rare earth permanent magnet provided in an embodiment of the present application.
[0044] The new energy vehicle provided in the embodiment of the present application has a motor that includes the rare earth permanent magnet provided in the present application, thereby significantly improving the energy conversion efficiency of the motor and improving the performance and endurance of the vehicle.
[0045] The following describes the invention in conjunction with specific embodiments.
[0046] Example 1
[0047] This embodiment provides a method for preparing a terbium-based target material, comprising the following steps:
[0048] S11: putting the first terbium powder (oxygen content less than 500 ppm, metal impurity content less than 100 ppm, D50=6 μm, spherical), the second terbium powder (oxygen content less than 500 ppm, metal impurity content less than 100 ppm, D50=0.8 μm, flake) and aluminum hydride into a planetary ball mill, and mixing them uniformly to obtain a mixed powder;
[0049] Wherein, the weight ratio of the first terbium powder to the second terbium powder is 7 / 3;
[0050] The amount of aluminum hydride added is 1.5% of the total weight of the first terbium powder and the second terbium powder;
[0051] S12: filling the mixed powder into a silicone mold by vibration, and then placing it in a cold isostatic press, initially pressurizing it to 70 MPa for 3 minutes, and then pressurizing it to 150 MPa for 3 minutes to obtain a first green body;
[0052] S13: adding carbon powder, aluminum oxide, silicon nitride, and polyvinyl pyrrolidone to ethanol and mixing them by ball milling, and then adding hydroxypropyl methylcellulose and polyethyleneimine and mixing them evenly to obtain a refining agent slurry;
[0053] Wherein, the weight ratio of refiner: aluminum oxide and silicon nitride is 2 / 1;
[0054] The weight ratio of polyvinyl pyrrolidone, hydroxypropyl methylcellulose, polyethyleneimine, carbon powder, refiner and solvent is 3 / 4 / 5 / 1 / 2 / 85;
[0055] S14: spraying the refiner slurry onto the surface of the first green body, then placing it in a vacuum sintering furnace, evacuating to 0.01 Pa, introducing nitrogen, and heating to 800° C. for 10 h, then heating to 1100° C. for 18 h, and finally cooling to below 50° C. at a rate of 50° C. / h to obtain a second green body;
[0056] S15: placing the second blank in an annealing furnace, evacuating the furnace to 0.01 Pa, starting to raise the temperature to 850°C, and introducing a mixed gas of water vapor and nitrogen (the volume content of water vapor is 5%), and keeping the temperature for 2.5 hours to obtain a terbium-based target.
[0057] Example 2
[0058] This embodiment provides a method for preparing a terbium-based target material, which is different from Embodiment 1 in that:
[0059] In step S11, magnesium hydride is replaced with aluminum hydride.
[0060] Example 3
[0061] This embodiment provides a method for preparing a terbium-based target material, which is different from Embodiment 1 in that:
[0062] In step S11, the amount of aluminum hydride added is 0.1% of the total weight of the first terbium powder and the second terbium powder.
[0063] Example 4
[0064] This embodiment provides a method for preparing a terbium-based target material, which is different from Embodiment 1 in that:
[0065] In step S11, the amount of aluminum hydride added is 3% of the total weight of the first terbium powder and the second terbium powder.
[0066] Example 5
[0067] This embodiment provides a method for preparing a terbium-based target material, which is different from Embodiment 1 in that:
[0068] In step S13, the weight ratio of polyvinyl pyrrolidone, hydroxypropyl methylcellulose, polyethyleneimine, carbon powder, refiner and solvent is 0.5 / 2.0 / 1.5 / 0.5 / 0.5 / 95.
[0069] Example 6
[0070] This embodiment provides a method for preparing a terbium-based target material, which is different from Embodiment 1 in that:
[0071] In step S13, the weight ratio of polyvinyl pyrrolidone, hydroxypropyl methylcellulose, polyethyleneimine, carbon powder, refiner and solvent is 5 / 8 / 7 / 2 / 3 / 75.
[0072] Example 7
[0073] This embodiment provides a method for preparing a terbium-based target material, which is different from Embodiment 1 in that:
[0074] In step S15, the volume content of water vapor is 1%.
[0075] Example 8
[0076] This embodiment provides a method for preparing a terbium-based target material, which is different from Embodiment 1 in that:
[0077] In step S15, the volume content of water vapor is 10%.
[0078] Comparative Example 1
[0079] This comparative example provides a method for preparing a terbium-based target material, which differs from Example 1 in that:
[0080] In step S11, aluminum hydride is not added.
[0081] Comparative Example 2
[0082] This comparative example provides a method for preparing a terbium-based target material, which differs from Example 1 in that:
[0083] Step S13 is not included;
[0084] Step S14: placing the first green body in a vacuum sintering furnace, evacuating to 0.01Pa, introducing nitrogen, heating to 800°C and keeping it for 10h, then heating to 1100°C and keeping it for 18h, and then cooling down to below 50°C at a rate of 50°C / h to obtain a second green body.
[0085] Comparative Example 3
[0086] This comparative example provides a method for preparing a terbium-based target material, which differs from Example 1 in that:
[0087] Step S13: adding aluminum oxide, silicon nitride and polyethylene glycol to ethanol and mixing them by ball milling, and then adding hydroxypropyl methylcellulose and mixing them evenly to obtain a refiner slurry;
[0088] Wherein, the weight ratio of aluminum oxide to silicon nitride is 2 / 1;
[0089] The weight ratio of polyethylene glycol, hydroxypropyl methylcellulose, thinning agent and solvent is 3 / 10 / 2 / 85.
[0090] Comparative Example 4
[0091] This comparative example provides a method for preparing a terbium-based target material, which differs from Example 1 in that:
[0092] In step S15, the mixed gas of water vapor and nitrogen is replaced with nitrogen.
[0093] Comparative Example 5
[0094] This comparative example provides a method for preparing a terbium-based target material, which differs from Example 1 in that:
[0095] In step S15, the second terbium powder is not added.
[0096] Comparative Example 6
[0097] This comparative example provides a method for preparing a terbium target, comprising the following steps:
[0098] S1: Place terbium powder (oxygen content less than 500ppm, metal impurity content less than 100ppm, D50=6μm, spherical) in a vacuum melting furnace, heat to 1450℃ at a frequency of 5000 Hz, melt and keep warm for 30 minutes to form terbium melt;
[0099] S2: Casting the terbium melt into a water-cooled mold, controlling the cooling rate at 50°C / s by controlling the water flow rate, taking out the ingot from the mold after cooling, and then machining to obtain the terbium target.
[0100] Related performance test analysis:
[0101] 1. The cross-sectional morphology of the terbium-based target prepared in Example 1 was tested using a scanning electron microscope. The test results are as follows: Figure 2 As shown:
[0102] from Figure 2 It can be seen that the terbium-based target is composed of large grains and small grains tightly packed in appropriate proportions, with high density and low porosity.
[0103] 2. The actual density of the terbium-based targets prepared in Examples 1 to 8 and Comparative Examples 1 to 6 was tested by the Archimedes density test method. The theoretical density was used as a reference. Relative density = actual density / theoretical density × 100%.
[0104] 3. The O content of the terbium-based targets prepared in Examples 1 to 8 and Comparative Examples 1 to 6 was tested using an oxygen and nitrogen analyzer.
[0105] 4. The terbium-based targets prepared in Examples 1 to 4 and Comparative Examples 1 and 6 were sputtered and coated by magnetron sputtering equipment to deposit a terbium-based metal layer on the surface of the NdFeB substrate, and then diffused at 900° C. for 4 h to obtain a rare earth permanent magnet; according to GBT 3217-2013 “Magnetic Test Methods for Permanent Magnetic Materials”, the magnetic properties of the rare earth permanent magnets corresponding to Examples 1 to 4 and Comparative Examples 1 and 6 were tested;
[0106] The test results are shown in Table 1 below:
[0107] Table 1
[0108]
[0109] As can be seen from Table 1, the oxygen content of the terbium-based target materials of Examples 1 to 4 is significantly lower than that of Comparative Example 1, and the remanence, coercive force and maximum magnetic energy product of the rare earth permanent magnets corresponding to the terbium-based targets of Examples 1 to 4 are significantly greater than those of Comparative Example 1, indicating that the aluminum hydride or magnesium hydride added in the embodiments of the present application generates hydrogen to form a reducing atmosphere during the sintering process, which can prevent terbium metal oxidation, so the oxygen content of the terbium target material is significantly lower. In addition, the appropriate amount of magnesium and aluminum generated can reduce the melting point of the diffusion source, increase the wettability between the diffusion source and the surface of the NdFeB magnet, thereby quickly forming a continuous diffusion channel and promoting terbium diffusion, so the magnetic properties of the rare earth permanent magnet are better.
[0110] The oxygen content of the terbium-based target of Example 1 is significantly lower than that of Comparative Examples 2 and 3, and the relative density of the terbium-based target of Example 1 is significantly higher than that of Comparative Example 2, indicating that the refiner of the embodiment of the present application can form high grain boundary strength during the sintering process, inhibit grain growth, thereby making the target material grain structure finer and more uniform, and the density of the terbium-based target is higher. In addition, the polyvinyl pyrrolidone in the refiner slurry decomposes during the sintering process, which helps to remove oxygen and impurities on the surface of the blank, and the amine group in the polyethyleneimine decomposes during the sintering process to play a reducing role to prevent terbium oxidation. The carbon powder reacts with water vapor during the annealing process to generate hydrogen and carbon monoxide, creating a reducing environment to prevent oxidation of the surface of the blank, so the oxygen content of the terbium-based target of Example 1 is lower than that of Comparative Example 3.
[0111] The relative density of the terbium target of Example 1 is higher than that of Comparative Example 4, and the oxygen content of the terbium-based target of Example 1 is significantly lower than that of Comparative Example 4, indicating that the embodiment of the present application adopts a mixed gas of water vapor and nitrogen for annealing, and the water vapor in the mixed gas can heat the blank quickly and evenly, promote grain boundary migration, refine the grains, and at the same time regulate the reaction rate, making the crystallization process more controllable and the particle size more uniform, so the relative density of the terbium-based target is higher. In addition, water vapor reacts with carbon powder to generate hydrogen and carbon monoxide, creating a reducing environment to prevent oxidation of the surface of the blank, so the oxygen content of the terbium-based target is low.
[0112] The oxygen content of the terbium target material in Example 1 is significantly lower than that in Comparative Example 6, and the relative density of the terbium target material in Example 1 is significantly higher than that in Comparative Example 6, indicating that the terbium-based target material prepared in the examples of the present application is better than that prepared by melting and casting.
[0113] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a terbium-based target, characterized in that: The following steps are involved: The first terbium powder, the second terbium powder and the reducing agent are ball-milled and mixed to form a mixed powder; the first terbium powder is spherical and has a particle size of 2-10 μm; the second terbium powder is flake or irregular in shape and has a particle size of 0.5-1 μm; isostatically pressing the mixed powder to obtain a first green body; Spraying a refiner slurry onto the surface of the first green body and then sintering the green body to obtain a second green body; The second green body is subjected to microcrystallization annealing treatment, and then machined to obtain a terbium-based target; Wherein, the reducing agent is selected from at least one of calcium hydride, magnesium hydride and aluminum hydride; The amount of the reducing agent added is 0.1-3% of the total weight of the first terbium powder and the second terbium powder; The refiner slurry comprises polyvinyl pyrrolidone, hydroxypropyl methylcellulose, polyethyleneimine, carbon powder, refiner and solvent in a weight ratio of (0.5-5) / (2-8) / (1.5-7) / (0.5-2) / (0.5-3) / (75-95); The atmosphere of the microcrystallization annealing treatment is a mixture of water vapor and nitrogen, the temperature is 800-900° C., and the time is 2-3 hours; the volume content of water vapor in the mixture is 1-10%.
2. The method for preparing a terbium-based target according to claim 1, characterized in that: The refiner comprises aluminum oxide and silicon nitride in a weight ratio of (2.5-1.5) / 1; And / or, the solvent is selected from ethanol or terpineol.
3. The method for preparing a terbium-based target according to claim 1, characterized in that: The weight ratio of the first terbium powder to the second terbium powder is (6-8) / (2-4).
4. The method for preparing a terbium-based target according to any one of claims 1 to 3, characterized in that: The sintering treatment steps include: under vacuum or inert atmosphere conditions, first heating to 700-900° C. and keeping the temperature for 6-12 hours, then continuing to heat to 1050-1150° C. and keeping the temperature for 12-24 hours, and then cooling down to below 50° C. at a rate of 40-60° C. / h.
5. A terbium-based target material, characterized in that: The terbium-based target material is prepared by the method for preparing the terbium-based target material according to any one of claims 1 to 4; wherein the oxygen content of the terbium-based target material is lower than 1000 ppm and the relative density is higher than 98.5%.
6. A rare earth permanent magnet, characterized in that: It comprises a NdFeB magnet and a terbium-based metal layer deposited on the surface of the NdFeB magnet, wherein the terbium-based metal layer is obtained by sputtering and coating the terbium-based target material according to claim 5.
7. A new energy vehicle, comprising a motor, characterized in that: The motor comprises the rare earth permanent magnet according to claim 6.
Citation Information
Patent Citations
Preparation method for rolling processing of tungsten-titanium alloy target material
CN106319463A
Method of preparing high-performance neodymium iron boron magnet by terbium powder
CN110233039A
Tantalum powder for powder metallurgy tantalum target and tantalum target
CN114888279A